(untitled) (Al-Academy, 2023)
The current research dealt with contrastive structures and the culture of reception in the design of interior spaces as embodying a rhetorical aspect that reveals formal values related to the meanings of beauty through the mechanisms of symbolism and interpretation that drives mental behavior and is in harmony with intellectual data and its performance function.Hence, the research in the first chapter dealt with the research problem, the need for it, and the extent of the necessity that calls for studying contrastive structures in interior design and architecture, and touching and searching for what is the paradox and its representations for the recipient, in which the interior designer plays an active role in presenting the best creative design product for the recipient.The current research went to a specific goal embodied by: (discovering the contrast of design structures that would enhance the design production with an idea characterized by strength for the design of the interior space through the mutual relationship that positively affects receiving the interior design discourse.)As for the theoretical framework within the course of the second chapter, the research formed two scientific sections, in which the first topic was linked to the concept of contrastive structures.While the second topic came with an extensive study on the concept of reception theory. The topic also dealt with the horizon of reception and the aesthetic distance.From the foregoing, the theoretical framework resulted in a set of indicators adopted by the researcher as theoretical data in his research procedures within the requirements of the third chapter. Spaces were chosen from three countries (Iraq, Kuwait, Bahrain) in an intentional manner by defining data and content to reach results and conclusions that contributed to its success by building the data analysis tool. Which the researcher deduced from the theoretical framework indicators